2021
DOI: 10.1186/s13048-021-00880-3
|View full text |Cite
|
Sign up to set email alerts
|

An overview of FSH-FSHR biology and explaining the existing conundrums

Abstract: FSH was first identified in 1930 and is central to mammalian reproduction. It is indeed intriguing that despite being researched upon for about 90 years, there is still so much more to learn about FSH-FSHR biology. The purpose of this review is to provide an overview of current understanding of FSH-FSHR biology, to review published data on biological and clinical relevance of reported mutations, polymorphisms and alternately spliced isoforms of FSHR. Tissue-resident stem/progenitor cells in multiple adult tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 91 publications
1
29
0
1
Order By: Relevance
“…Earlier studies have reported similar results that alternately spliced Fshr3 is modulated in association with the stem cells activity in both the ovary [28] and testes [29]. These results of direct action of FSH on tissue-resident stem cells via Fshr3 rather than canonical Fshr1 were recently reviewed [23,24].…”
Section: Effect Of Xar ™ Compared To Fsh On Ovarian Folliclesmentioning
confidence: 53%
See 1 more Smart Citation
“…Earlier studies have reported similar results that alternately spliced Fshr3 is modulated in association with the stem cells activity in both the ovary [28] and testes [29]. These results of direct action of FSH on tissue-resident stem cells via Fshr3 rather than canonical Fshr1 were recently reviewed [23,24].…”
Section: Effect Of Xar ™ Compared To Fsh On Ovarian Folliclesmentioning
confidence: 53%
“…We have earlier reported a direct action of XAR ™ on stem cells in human blood [22]. The tissue-resident VSELs express pluripotent markers along with ERα, ERβ and FSHR in multiple tissues [23,24] and thus it was of interest to study if XAR ™ could exert similar effects like FSH on the ovaries. In the present study, the effects of XAR ™ and FSH were compared on numbers of primordial and growing follicles in adult mouse ovary and correlated with circulatory levels of Anti Mullerian Hormone (AMH).…”
Section: Introductionmentioning
confidence: 99%
“…However, exposure to FSH elevated methylation levels and initiated chromatin remodeling in those cells, accompanied by an altered meiotic function. Presumably, this occurred via the effect of FSH on granulosa cells surrounding the oocyte ( Yu et al, 2022 ) ( Bhartiya and Patel, 2021 ), known to express receptors for FSH, but this needs to be further demonstrated. Importantly, the effect of FSH on pre-pubertal oocytes is only partial.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 1, 2022. ; https://doi.org/10.1101/2022.08.01.502312 doi: bioRxiv preprint Glycoprotein hormones and their receptors play central roles in regulating body development, reproduction and metabolism 44,45 . Being an essential part of endocrine system, they are involved in many endocrine diseases such as infertility, OHSS, male-limited precocious puberty 5,46 , Graves' and Hashimoto's diseases 47,48 . In this paper, we report the structures of full-length FSHR in both inactive and active states.…”
Section: Discussionmentioning
confidence: 99%
“…FSH acts through FSHR, which is mainly expressed in gonads (ovaries in female and testes in male) 3 . Mutations in human demonstrate that aberrant signaling of FSH-FSHR can lead to serious diseases 4, 5 , especially infertility and ovarian hyperstimulation syndrome (OHSS). Recently, much more evidence have been found that the function of extra gonadal FSHR is also closely relevant to Alzheimer’s disease and cancers 6, 7 .…”
Section: Introductionmentioning
confidence: 99%